Wybrane zagadnienia kosztowo-optymalnego planowania eksperymentów w zagadnieniu regresji - Kuźmiński, Łukasz (The Selected Issues of Cost-Optimal Design of Experiments in Regression, 2006)
This paper presents the bases of the theory of cost-optimal designs of experiment for the estimation of parameters of regression model. In this theory we can differentiate two cases. In the first case the total cost of experiment depends only on the number of observations. In the second case the total cost of experiment is additionally dependent on the allocation of points in the experimental area, in which the observations are done. In the article it is shown that the cost-optimal designs can be obtained according to two approaches. Both approaches are illustrated with examples.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 58-73